1994
DOI: 10.1083/jcb.127.6.1717
|View full text |Cite
|
Sign up to set email alerts
|

Altered gene expression in neurons during programmed cell death: identification of c-jun as necessary for neuronal apoptosis.

Abstract: Abstract. We have examined the hypothesis that neuronal programmed cell death requires a genetic program; we used a model wherein rat sympathetic neurons maintained in vitro are deprived of NGF and subsequently undergo apoptosis. To evaluate gene expression potentially necessary for this process, we used a PCR-based technique and in situ hybridization; patterns of general gene repression and selective gene induction were identified in NGF-deprived neurons. A temporal cascade of induced genes included "immediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
531
9
6

Year Published

1996
1996
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 793 publications
(577 citation statements)
references
References 71 publications
30
531
9
6
Order By: Relevance
“…irradiation, heat shock (Davis, 1994;Zanke et al, 1996) and trophic factor withdrawal from PC12 cells (Xia et al, 1995). cJUN, the downstream target of JNK, was also shown to be critical for apoptosis in SCG cultures following NGF removal (Estus et al, 1994). In the current study, p21 did not inhibit death induced by trophic factor withdrawal, u.v.…”
Section: Discussionmentioning
confidence: 42%
“…irradiation, heat shock (Davis, 1994;Zanke et al, 1996) and trophic factor withdrawal from PC12 cells (Xia et al, 1995). cJUN, the downstream target of JNK, was also shown to be critical for apoptosis in SCG cultures following NGF removal (Estus et al, 1994). In the current study, p21 did not inhibit death induced by trophic factor withdrawal, u.v.…”
Section: Discussionmentioning
confidence: 42%
“…Initial studies using PC12 cells and sympathetic neurons showed that inhibition of c-Jun activity, either by microinjection of antibodies against c-Jun or expression of dominant negative mutant forms of the protein protects the cells from nerve growth factor (NGF) withdrawal-induced apoptosis (Estus et al, 1994;Ham et al, 1995;Xia et al, 1995). Furthermore, ectopic expression of c-Jun is su cient to drive sympathetic neurons into apoptosis in the absence of external stimuli (Ham et al, 1995).…”
Section: Jun As a Mediator Of Apoptosismentioning
confidence: 99%
“…One of the first regulated genes to be identified was the basic/leucine zipper transcription factor c-Jun, a member of the AP-1 family. The level of the c-jun mRNA and c-Jun protein increases rapidly in sympathetic neurons after NGF withdrawal, and microinjection of neutralizing antibodies against c-Jun or expression of a c-Jun dominant-negative mutant protects sympathetic neurons against NGF withdrawal-induced death, 4,5 as does conditional knockout of the c-jun gene in sympathetic neurons isolated from mice with a floxed c-jun gene. 6 These observations supported the idea that NGF withdrawal-induced death involves the transcriptional induction of genes that activate the cell death programme.…”
Section: Ngf Withdrawal-induced Death Requires Transcription and Invomentioning
confidence: 99%